Exploring Brand Management of Emerging-Markets Small and Medium Enterprises Operating in the Business to Business Industry - Raki, Samira (Universiti Malaysia Sarawak (UNIMAS), 2020)
Emerging Markets SMEs operate in a heightened competitive environment where external support such as the government is of great importance to develop their brands and remain competitive. Thus, the purpose of this thesis is to explore B2B brand management in emerging markets SMEs from the stakeholders’ perspective, and consequently to develop a B2B Brand Management Framework, whereby SMEs can achieve as well as sustaining competitive advantage, and realise B2B brand performance. In this respect, this study identified stakeholder theory as an underlying theory to this inquiry and explored brand building process from the perspective of the SME and the government. Hence, this study employed semi-structured interviews under the case study approach. The case study investigated eight SMEs operating in the B2B industry and three governmental agencies in charge of SMEs brand development programmes in Malaysia. The findings highlighted the major role played by the government in enhancing the brand performance of the beneficiaries and have led to the development of Stakeholders B2B Brand Management Framework. The framework suggested that brand building in the B2B context requires the identification of two dimensions: (1) understanding of the brand, and (2) branding process. Finally, this study has contributed by linking stakeholder theory with the B2B branding and consequently proposing Stakeholders B2B Brand Management Framework to respond to the increased demand of more B2B branding frameworks.